2024
DOI: 10.1051/0004-6361/202347787
|View full text |Cite
|
Sign up to set email alerts
|

Cosmic evolution of radio-excess active galactic nuclei in quiescent and star-forming galaxies across 0 < z < 4

Yijun Wang,
Tao Wang,
Daizhong Liu
et al.

Abstract: Radio-excess active galactic nuclei (radio-AGNs) are essential to our understanding of both the physics of black hole (BH) accretion and the interaction between BHs and host galaxies. Recent deep and wide radio continuum surveys have made it possible to study radio-AGNs down to lower luminosities and up to higher redshifts than previous studies, and are providing new insights into the abundance and physical origin of radio-AGNs. Here we focus on the cosmic evolution, physical properties, and AGN-host galaxy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 129 publications
0
1
0
Order By: Relevance
“…A wellestablished correlation, spanning up to 5 orders of magnitude, exists between far-infrared and radio emission from galaxies (e.g., Helou et al 1985;Condon et al 1991aCondon et al , 1991bAppleton et al 2004;Gim et al 2019). The intense radio emission, deviating significantly from this correlation, is attributed to the influence of AGN activities (e.g., Yun et al 2001;Calistro Rivera et al 2017;Wang et al 2024). However, recent studies have shown that radio excess can only collect the most radioloud AGNs (e.g., Morić et al 2010;Solarz et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…A wellestablished correlation, spanning up to 5 orders of magnitude, exists between far-infrared and radio emission from galaxies (e.g., Helou et al 1985;Condon et al 1991aCondon et al , 1991bAppleton et al 2004;Gim et al 2019). The intense radio emission, deviating significantly from this correlation, is attributed to the influence of AGN activities (e.g., Yun et al 2001;Calistro Rivera et al 2017;Wang et al 2024). However, recent studies have shown that radio excess can only collect the most radioloud AGNs (e.g., Morić et al 2010;Solarz et al 2019).…”
Section: Introductionmentioning
confidence: 99%